Improving Student Learning Outcomes Through an Activity-Based Interactive Learning Model in the Subject of Civics - Kartika Dhea Sabrina (International Journal of Students Education, 2024)
This research aims to determine the role of activity-based interactive learning models on student learning outcomes in PKN subjects. Then to find out how the application of interactive learning models can improve student learning outcomes. This research uses a systematic literature (SR) method obtained from journals related to improving student learning outcomes through activity-based interactive learning models in PKN subjects. The results of the research show that in as many as 4 journals it is known that the activity-based interactive learning model in PKN subjects can improve student learning outcomes. Based on the research conducted, it can be concluded that after carrying out this research, the application of the activity-based interactive learning model to improve student learning outcomes can be done by starting with making a learning implementation plan (RPP), determining the concept of the material to be taught to students, searching and formulating problems that are in accordance with this concept, as well as planning appropriate or suitable learning strategies.